ASPEK HUKUM TINDAK PIDANA PENYIMPANAN/ BARANG KEBUTUHAN POKOK DAN BARANG PENTING - Abdi I; Syarif Fadillah; Damrah Mamang (Jurnal Hukum Jurisdictie, 2019)
Abdi 2017, Review Of The Criminal Law On The Storage Of Basic Goods and Essential Goods.The crime of storing basic goods is a form of economic crime that occurs in the community but is rarely touched by law enforcement. Storage activities are carried out at a time when the food sector in Indonesia is experiencing a crisis of food sources caused by overexploitation or poor natural conditions. As a result, inflation is out of control. The question is how is the analysis of criminal law in Indonesia in storing basic goods and essential goods? And what is the form of criminal responsibility for the storage of basic goods and essential goods? In the discussion of this thesis, the method used is a juridical normative research method using the conseptual apparach approach. Criminal liability of criminal perpetrators of the crime of storing basic goods and essential goods and accounted for to people or corporations as legal subjects. Because those who can make mistakes are people as well as corporations. This person or corporation is also included in the investigation of business actors in the Trade Act so that they can be held accountable for criminal acts. The criminal arrangement of the criminal act of storing basic and essential goods is regulated in Law No. 7 of 2014 on trade in law No. 18 of 2012 on food and Presidential Regulation No. 71 of 2015 on the storage of basic goods and essential goods and related laws and regulations related to others.